“Accidental” Language Acquisition: A Study of Indonesian Youth Learning English Informally through Online Gaming and Streaming Culture - Mariama Bah; Samira Mohammed; Marcia Hendriks (Yayasan Adra Karima Hubbi, 2025)
Background. Informal digital environments have become influential spaces for incidental language learning among young people, especially where formal classroom instruction alone may not adequately foster communicative fluency. Purpose. This study aimed to investigate how Indonesian youth acquire English incidentally through engagement in online gaming and streaming cultures. It focused on identifying the types of linguistic features acquired, the social-interactional mechanisms that facilitate learning, and the extent to which these informal experiences complement or exceed outcomes from formal English instruction. Method. A qualitative descriptive research design was employed using digital ethnography. Data were collected from 32 participants aged 13–22 through in-depth interviews, observation of online interactions, and discourse analysis of chat logs and voice communications over a three-month period. Results. The findings indicated that participants acquired functional vocabulary, pragmatic expressions, and increased communicative confidence primarily through authentic peer interaction, task-based collaboration, and the need to negotiate meaning during gameplay. Participants reported notable improvements in listening comprehension and speaking fluency, often perceiving faster progress in informal digital environments than in formal classroom settings. Conclusion. The study concludes that online gaming and streaming cultures function as dynamic and self-sustaining ecosystems for incidental English language learning. These environments provide rich exposure, strong motivation, and meaningful interactional demands that are frequently limited in school-based instruction.